ONLINE LEARNING DURING COVID 19 PANDEMIC: HOW SELF-REGULATED LEARNING STRATEGIES AFFECT STUDENT ENGAGEMENT? - Helsa Helsa; Krishervina Rani Lidiawati (Universitas Bunda Mulia, 2021)
The coronavirus disease 19 (COVID-19) pandemic has many impacts in educational setting, such as switching learning process into online. Online learning is not easy in Indonesia due to inadequate facilities and students who are still not able to be independent learner. Thus, self-regulated learning strategies can help students to be more engaged in the online learning process. The purpose of this study was to determine students' involvement in distance learning process during the pandemic in terms of students' ability to self-regulate in learning. This study involved 521 participants who were active students in distance learning during the COVID-19 pandemic, consisting of 161 men and 360 women aged 18-21 years. The results showed a significant correlation between self-regulated learning and student engagement (r = .748, p = 0.000). The results of linear regression test obtained significant result F (df1, df2) = 659.20, p = .000). The regression coefficient R2 shows that self-regulated learning influenced 55.9% on student engagement, then 44.1% is influenced by other factors outside of self-regulated learning. In conclusion, this research shows significant effect of SRL on student engagement.